Analisis Kebutuhan Informasi Tenaga Pendidik Pada Anak Penyandang Disleksia Di Sekolah Luar Biasa Amal Mulia Yayasan Dharma Bhakti Kesejahteraan Sosial Kota Bengkulu - Ananda, Milla; Timoria Samosir, Fransiska; Sa'diyah, Lailatus (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Educators have a very important role to improve the ability of students in the teaching and learning process. The tasks and roles of educators can be achieved well if educators have qualified information needs. This research focuses on the information needs of educators in educating dyslexic students. The purpose of this study was to determine the information needs of educators in dyslexic children at SLB Amal Mulia Yayasan Dharma Bhakti Social Welfare Bengkulu City in the learning process. The qualitative method is descriptive and has 3 information as data sources, observation interview techniques and documentation. The results showed in terms of psychological needs, affective needs, cognitive needs where all aspects of educators have implemented well, but there is still a need for further development in accessing information needs. The information needs of SLB Amal Mulia educators, Yayasan Dharma Bhakti Social Welfare Bengkulu City, have good enough knowledge in educating dyslexic students even though they do not have basic skills as special educators. This can be seen from the ability of educators to access information needs, evaluate information needs and use information as well as possible to educate dyslexic students in the teaching and learning process to run effectively and efficiently.